Topography Effects on Rainfall Characteristics in Bandung City and Cilacap Regency for the 2016-2020 Period - Afghani, Fadhli Aslama; Mashuri, Imawan; Khirtin, Ramadoni; Cahyo, Muhammad Adi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Topography and rainfall correlate with each other. Therefore, this study aims to determine the effect of topography on rainfall characteristicss in the Cilacap and Bandung areas. The research method used is a descriptive statistical analysis of average monthly, seasonal, and annual rainfall. In addition, time series and regression tests were carried out using the SPSS application. The data used is the daily rainfall data period of 2016–2020. The results of the descriptive analysis show that the variability of monthly rainfall in Bandung is higher than in Cilacap, with a value range that is 113.6–643.82 mm/month for Bandung and 92.1-355.56 mm/month for Cilacap. Global climate dynamics for instance apparent sun motion, Monsoon, ITCZ, ENSO, and IOD, as well as local weather systems like valley winds, also affect seasonal and annual rainfall variability in Bandung and Cilacap. The rainfall time series test produces values that are not stationary concerning the variance but stationary concerning the average. A simple linear regression test shows the effect of a topography of 55.2% on rainfall. The purpose of simple linear regression is to understand and model the relationship between two variables: the independent variable (topography) and the dependent variable (rainfall characteristics).